157 Evaluating Interest in Clinical Trial Participation for the Treatment of Pediatric Food Allergy. (April 2022) - Catlin, Perry A.; Van Hecke, Amy; Assa'ad, Amal; Gupta, Ruchi
Abstract : OBJECTIVES/GOALS: Roughly 8% of children in the United States have a diagnosed food allergy (FA). The ubiquity of most food allergens increases the potential for accidental exposures. Clinical trials (CT) are used to test novel treatments for FA. This project will evaluate the influence of biopsychosocial factors on interest in CT participation for pediatric FA. METHODS/STUDY POPULATION: This project is subsumed under the FORWARD study (5R01AI130348-04), a multisite study currently underway at four pediatric FA clinics across the United States. Eligible participants include patients and families who meet the following criteria: 1) New clinic visit presenting for a possible FA complaint and/or has a physician diagnosis in a follow-up clinic visit; 2) child is between the age of 6-months and 12 years at intake visit; 3) are English speaking, and 4) no history of developmental disorders. Parents are asked to complete an intake survey, followed by a series of quarterly surveys administered via REDCap. A single variable from the intake survey queries interest in CT participation; quarterly surveys assess FA knowledge, attitudes, health beliefs, and management practices. RESULTS/ANTICIPATED RESULTS: To date, 890 families have completed the intake survey. Working hypotheses include: 1) parents of older children and children with a higher condition severity rating will report greater levels of interest in CT participation; 2) parents with greater FA knowledge, more health management beliefs that support action, and less FA-related anxiety, will report greater levels of interest in CT participation; 3) relative to White families, African American families will be less interested in participating; 4) families with >1 child with FA will report greater levels of interest in CT participation; 5) families who are uninsured, low-SES, and are unemployed will report lower levels of interest in CT participation; and 6) families with higher educational attainment will report lower levels of interest in CT participation. DISCUSSION/SIGNIFICANCE: This study will advance decision science, address existing disparities, and have far-reaching clinical implications. This novel approach will enhance our ability to predict who is at the greatest risk of anaphylaxis and help healthcare providers identify families who could benefit from experimental treatment options for pediatric FA.